Optimizing Pricing Strategies to Maximize Profits for Balancing Service Providers in FCR-N and FCR-D Reserve Markets - Hossain, Amjad (My University, 2025)
The goal of this thesis is to determine how a 1 MW battery can profit in Finland’s frequency reserve markets with smart pricing strategies. It consists of two markets: FCR-N, run continuously and FCR-D which is brought in when there are unusual fluctuations in frequency. This work looks at how different pricing methods can change the profit a battery system earns. Using real data from Fingrid's 2024 frequency reserve markets, a battery operating model was run to provide the findings reported in this master's thesis. For FCR-N, two control methods were examined: a straightforward rule based one and an advanced approach using practical logic that responds to changes in prices and frequency. The easy-to-use model earned more profit, yet the market rules were better followed with the improved logic. A review of FCR-D was included, though a lack of activation data results in imprecise and less trustworthy findings. This study demonstrates that using a good strategy and precise information, battery systems may do well in FCR-N. Future work on the model could add battery aging as a factor, make the controlling system more complex and include the complete set of FCR-D activation data.
Keywords: pricing; simulation; optimisation; electricity market; profitability; batteries; fi=Sähkö- ja energiatekniikka|en=Electrical Engineering and Energy Technology|; Master´s Programme in Smart Energy